Perlindungan Hak Ekonomi Pencipta Lagu dalam Perspektif Maqāṣid al-Syarī’ah - Zuhdi, Irfan; Irfan, Irfan (Program Studi Hukum Ekonomi Syariah, 2025)
The high rate of copyright infringement in Indonesia, particularly concerning musical works, reflects a paradox between Islamic values that uphold justice and prevailing social practices that neglect the economic rights of creators. This study aims to evaluate the protection of the economic rights of songwriters under Law No. 28 of 2014 and Government Regulation No. 56 of 2021 through the lens of maqāṣid al-syarī‘ah. Employing a normative juridical approach and qualitative analysis of statutory regulations alongside classical and contemporary Islamic legal thought, the study finds that Indonesia’s copyright regulations align substantially with the principle of ḥifẓ al-māl (protection of wealth) and other core objectives of Islamic law. The protection encompasses exclusive rights, licensing procedures, and a royalty management system administered by collective management organizations. The findings highlight the importance of integrating positive law with Islamic ethical values to build a just, sustainable, and welfare-oriented legal framework. The implications of this study are expected to strengthen legal legitimacy, enhance public awareness, and encourage policymakers to adopt more proactive measures in protecting copyright.